1968
DOI: 10.1002/macp.1968.021150111
|View full text |Cite
|
Sign up to set email alerts
|

Solid state polymerization of zinc methacrylate

Abstract: Zinc methacrylate has been polymerized in the solid state by the post-irradiation technique a t 89.5OC. The polymer produced was less isotactic than that obtained from barium methacrylate dihydrate when polymerized under similar conditions. The tacticity of the poly(zinc methacrylate) differed markedly from the polymer produced in the liquid phase from methyl methacrylate or methacrylic acid. X-ray studies of the zinc methacrylate showed the monomer to have an orthorhombic unit cell with lattice constants of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Zinc isobutyrate was synthesized from isobutyric acid and zinc carbonate in water analogous to the procedure of the synthesis of zinc methacrylate as reported elsewhere . Briefly, 0.54 mL of isobutyric acid was dissolved in 2 mL of water, and then 0.27 g of zinc carbonate was added portionwise upon vigorous vortexing.…”
Section: Methodsmentioning
confidence: 99%
“…Zinc isobutyrate was synthesized from isobutyric acid and zinc carbonate in water analogous to the procedure of the synthesis of zinc methacrylate as reported elsewhere . Briefly, 0.54 mL of isobutyric acid was dissolved in 2 mL of water, and then 0.27 g of zinc carbonate was added portionwise upon vigorous vortexing.…”
Section: Methodsmentioning
confidence: 99%
“…However, there was no direct correlation and the differences were attributed to the spatial arrangements of the molecules in the crystalline lattice, although these were, in general, not known, i.e., a structural effect. Parrish and Kochanny [ 5 ] have also reported the polymerization of zinc methacrylate and Fydelor and Charlesby [6] the effect of high pressures on the polymerization of barium methacrylate. methacrylic acid in the solid state.…”
Section: Bowden O'donnell and Sothmanmentioning
confidence: 96%
“…methacrylic acid in the solid state. In particular they have demonstrated the reversible, inhibiting effect of pressure on the polymerization [ 5 ] , which they have interpreted as being due to a change in the mobility of defects in the solid. The relative importance of spatial arrangement and mobility and the nature of the mobility are probably the most important unresolved problems in solid-state polymerization.…”
Section: Bowden O'donnell and Sothmanmentioning
confidence: 97%
“…The degree of polymerization increased markedly with an increased number of defects in the crystalline lattice arising during dehydration. ization was studied by Parrish and Kochanny [232] . After grinding, the crystals of zinc methacrylate were irradiated from a 6oCo source at 195 K, and then polymerization was continued by heating at 362.5 K. It was found that the dose rate had no effect on the degree of change of monomer.…”
Section: Szalinska and Pietrzakmentioning
confidence: 99%